PENGARUH LOVE OF MONEY DAN IDEALISME TERHADAP PERSEPSI ETIS MAHASISWA AKUNTANSI UNIVERSITAS MUHAMMADIYAH PALOPO: THE EFFECT OF LOVE OF MONEY AND IDEALISME ON THE ETHICAL PERCEPTION OF ACCOUNTING STUDENTS MUHAMMADIYAH PALOPO UNIVERSITY - Adam, Nurfadilla; Junaidi, Junaidi; Ramadhan, Abid (Universitas Riau, 2023)
This study aims to determine the effect of love of money and idealism on students' ethical perceptions. The population in this study were students majoring in Accounting in Sulawesi Selatan district. The number of questionnaires processed in this study were 100 respondents. To test the hypothesis, the researcher used a structural equation modeling (SEM) approach using the AMOS software. The results of this study indicate that the love of money has a positive effect on idealism, and idealism has an effect on ethical perceptions, while the love of money has no effect on ethical perceptions.